2022
DOI: 10.3390/nu14204285
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Polysaccharides and Gut Microbiota Ecosystem

Abstract: The intestinal microbiota is a community of microorganisms that subsists within the gastrointestinal ecosystem [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…This was done to assess compliance by comparing the number of tablets provided and returned. DMB was administered as an adjuvant medical-nutritional treatment [41,42,45].…”
Section: Experimental Design and Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…This was done to assess compliance by comparing the number of tablets provided and returned. DMB was administered as an adjuvant medical-nutritional treatment [41,42,45].…”
Section: Experimental Design and Participantsmentioning
confidence: 99%
“…Tumor necrosis factor-alpha (TNF-α), and human proteolysis-inducing factor/dermcidin (PIF) were determined and analyzed as previously described [41,42,45].…”
Section: Plasma Cytokinesmentioning
confidence: 99%
See 1 more Smart Citation
“…SCFAs consist of free fatty acids with two to five carbons, such as acetic acid, propanoic acid, and butyric acid, participating in signal transmission, nutrition provision and many other healthy protection functions in human body [ 39 ]. During these processes, polysaccharides are involved in the balance of the gut microbiota and host as a kind of prebiotic [ 40 ]. In turn, the gut microbiota can influence the host digestive efficiency by altering the bioavailability of polysaccharides [ 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…The gut microbiota of mammals largely relies on dietary polysaccharides as an energy source, and most polysaccharides also require the participation of gut microbiota in degradation 18 . The dietary polysaccharides that reach the colon have a significant impact on the ecology and balance of gut microbiota 19 . Research has shown that AP can regulate the composition of gut microbiota, alter the concentration of short chain fatty acids in the intestinal lumen, improve chronic inflammation, and reduce intestinal permeability in high-fat induced mice 20 .…”
Section: Introductionmentioning
confidence: 99%